2015
DOI: 10.1016/j.ebiom.2015.07.034
|View full text |Cite
|
Sign up to set email alerts
|

A Five-miRNA Panel Identified From a Multicentric Case–control Study Serves as a Novel Diagnostic Tool for Ethnically Diverse Non-small-cell Lung Cancer Patients

Abstract: Circulating microRNAs (miRNAs) are promising biomarkers for cancer detection. However, multiethnic and multicentric studies of non-small-cell lung cancer (NSCLC) are lacking. We recruited 221 NSCLC patients, 161 controls and 56 benign nodules from both China and America. Initial miRNA screening was performed using the TaqMan Low Density Array followed by confirming individually by RT-qPCR in Chinese cohorts. Finally, we performed a blind trial from an American cohort to validate our findings. RT-qPCR confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 32 publications
4
75
1
Order By: Relevance
“…The remaining 88 articles were selected for full‐text reading, of which 71 articles were removed: 14 using disease controls, 16 without reporting sensitivity, specificity or AUC values, and 41 reporting in non‐Western countries. In the end, 17 studies evaluating the diagnostic performance of circulating miRNAs in serum or plasma for LC detection published between 2011 and 2017 (Tables and ) were eligible for this systematic review …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 88 articles were selected for full‐text reading, of which 71 articles were removed: 14 using disease controls, 16 without reporting sensitivity, specificity or AUC values, and 41 reporting in non‐Western countries. In the end, 17 studies evaluating the diagnostic performance of circulating miRNAs in serum or plasma for LC detection published between 2011 and 2017 (Tables and ) were eligible for this systematic review …”
Section: Resultsmentioning
confidence: 99%
“…Two of the 17 studies are nested case‐control studies, in which incident cases were identified during following up of a prospective cohort, controls were matched disease‐free individuals from the same cohort and blood samples collected at baseline (ie, prior to incidence and diagnosis) were analyzed. The other 15 studies are case‐control studies in which blood samples were taken after cancer diagnosis . Of the 17 studies, 11 evaluated individual miRNAs (Table ), two of which conducted independent validation .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that downexpression of miR-7 in NSCLC may be implicated in promoting cancer cell progress, and consequently results in NSCLC growth [19, 24], which were in line with our study results. In addition, miR-7 is a tissue-specific miR to be directly involved in NSCLC [25]. Low expression level of miR-7 was significantly correlated with LNM in patients with cervical cancer [26].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on their mRNA targets, miRNAs can act as oncogenes or tumor suppressor genes. 26,27 The changes of miRNA are involved in most aspects of cancer biology, including proliferation, apoptosis, migration, and invasion. [28][29][30] Therefore, miRNAs are usually viewed as a potential diagnostic and therapeutic tool.…”
Section: Discussionmentioning
confidence: 99%